2017
DOI: 10.7863/ultra.16.02087
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Aneurysms of the Membranous Ventricular Septum Without Residual Shunts: Systematic Review and Description of 3 Cases in Adults

Abstract: A ventricular septal defect is the most common congenital cardiac abnormality encountered in infants and children. Many of them survive through adulthood before diagnosis. Two-thirds of the cases involve the membranous part of the septum. In the absence of an interventricular shunt or concomitant cardiac surgery, guidelines for surgical intervention or resection of isolated aneurysms of the membranous septum are not well established. In this report, we discuss a multi-imaging modality approach for the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…An AVMS occurs below the septal leaflets of the tricuspid valve, and the absence of localized septal myocardium results in an aneurysm-like change that anatomically manifests as a fibrous wall sac protruding from the septal membrane into the right ventricular outflow tract. [ 17 , 18 ] The diagnosis is usually confirmed by echocardiography, cardiac magnetic resonance imaging, or computed tomography. In most cases, the AVMS itself is not hemodynamically significant, but the presence of local hemodynamic alterations and local ventricular wall motion abnormalities within this particular cystic structure leads to the risk of potential complications, such as rupture, thrombosis, aortic valve prolapse, tricuspid valve insufficiency, right ventricular outflow tract obstruction, endocarditis, and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…An AVMS occurs below the septal leaflets of the tricuspid valve, and the absence of localized septal myocardium results in an aneurysm-like change that anatomically manifests as a fibrous wall sac protruding from the septal membrane into the right ventricular outflow tract. [ 17 , 18 ] The diagnosis is usually confirmed by echocardiography, cardiac magnetic resonance imaging, or computed tomography. In most cases, the AVMS itself is not hemodynamically significant, but the presence of local hemodynamic alterations and local ventricular wall motion abnormalities within this particular cystic structure leads to the risk of potential complications, such as rupture, thrombosis, aortic valve prolapse, tricuspid valve insufficiency, right ventricular outflow tract obstruction, endocarditis, and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…A closer follow-up is advised because of potential complications, and early repair is a consideration with evolving device-based interventions. 53 Bonvicini et al reported the dilatation of an aneurysm of the ventricular membranous septum without an interventricular shunt. 18 It should be considered that right ventricular outflow tract obstruction may also occur in patients with a large aneurysm of the ventricular membranous septum without a shunt.…”
Section: Recommendation Regarding Patients With An Aneurysm Of the Ve...mentioning
confidence: 99%
“…Close clinical and echocardiographic follow‐up was scheduled at 6 months, and subsequently every 9–12 months. If suspicious symptoms or echocardiographic changes will be reported, multimodality imaging and multidisciplinary reassessment will be performed, and surgical treatment might be considered 1,2 …”
Section: Figurementioning
confidence: 99%